The Silk Purse: Creating an Electronic Reserve System That Works for You and Your Library - Ellern, Gillian (Jill) D. (1999)
This presentation was made to the annual meeting of the IT staff in colleges and universities in North Carolina. Because audience members were not library staff/faculty, some of the presentation is about introducing these non-librarians to what reserves in the library involve and why it is important to students and faculty. WCU and UNCG librarians talked about how they created these systems themselves before the library’s ILS systems included this software, proxy access/security, and procedures.